Polymorphisms of the Multidrug Pump ABCG2: A Systematic Review of Their Effect on Protein Expression, Function, and Drug Pharmacokinetics - Heyes, Niall; Kapoor, Parth; Kerr, Ian D. (Drug metabolism and disposition, 2018)
The widespread expression and polyspecificity of the multidrug ABCG2 efflux transporter make it an important determinant of the pharmacokinetics of a variety of substrate drugs. Null ABCG2 expression has been linked to the Junior blood group. Polymorphisms affecting the expression or function of ABCG2 may have clinically important roles in drug disposition and efficacy. The most well-studied single nucleotide polymorphism (SNP), Q141K (421C>A), is shown to decrease ABCG2 expression and activity, resulting in increased total drug exposure and decreased resistance to various substrates. The effect of Q141K can be rationalized by inspection of the ABCG2 structure, and the effects of this SNP on protein processing may make it a target for pharmacological intervention. The V12M SNP (34G>A) appears to improve outcomes in cancer patients treated with tyrosine kinase inhibitors, but the reasons for this are yet to be established, and this residue’s role in the mechanism of the protein is unexplored by current biochemical and structural approaches. Research into the less-common polymorphisms is confined to in vitro studies, with several polymorphisms shown to decrease resistance to anticancer agents such as SN-38 and mitoxantrone. In this review, we present a systematic analysis of the effects of ABCG2 polymorphisms on ABCG2 function and drug pharmacokinetics. Where possible, we use recent structural advances to present a molecular interpretation of the effects of SNPs and indicate where we need further in vitro experiments to fully resolve how SNPs impact ABCG2 function.